Graphene oxide embedded sol–gel (GOSG) film as a SALDI MS substrate for robust metabolite fingerprinting1. Issue 70 (31st July 2015) - Lee, Gwangbin; Bae, Sang-Eun; Huh, Seong; Cha, Sangwon
<x xml:space="preserve">Abstract</x> A graphene oxide embedded sol–gel (GOSG) film was utilized as a substrate for surface-assisted laser desorption/ionization mass spectrometry (SALDI MS).